Security mechanism for wireless Mobile Ad Hoc Networks (MANET) - Abdul Rahman Sidek, Diana (2006)
This report describes the security mechanism of secret key cryptography for wireless ad hoc network. This project uses LabVIEW (version 6.0) a graphical programming software by National Instrument. The security mechanism consists of encryption and decryption method as being implemented using LabVIEW software. The wireless ad hoc network comprises of wireless mobile nodes that can freely and dynamically selforganize into arbitrary and temporary network topologies. It advantages is include the speed of connection setup, and ease of removal of services or users. Today, the military tactical operations are still the main application of ad hoc networks. This report provides an overview of wireless ad hoc networks, wireless threats, cryptography background and the security algorithms for this encryption method. The One Time Pad algorithm and Caesar Cipher algorithms are implemented using LabVIEW software. These algorithms are chosen because they are suitable for low bit rate data. The purpose of this project is to implement secure mechanism for data transfer in wireless ad hoc network.